Comparison of overall survival and disease-free survival for breast-conserving surgery and mastectomy in breast cancer patients receiving neoadjuvant therapy: a matched case-control study from two institutions - Du, Xueqian; Zhang, Senyan; Li, Yilu; Li, Yue; Feng, Yueqing (Frontiers in Oncology, 2026)
BackgroundNeoadjuvant therapy (NAT) has been increasingly promoted for treating early-stage breast cancer (BC), which significantly improves the adoption of breast-conserving surgery (BCS). However, concerns related to the oncological safety of BCS versus mastectomy remain unelucidated. The present study compared survival outcomes between patients treated with BCS and those treated with mastectomy after NAT through stratified analyses.MethodsThe study included female BC patients who underwent radical surgery after NAT at the Peking University First Hospital and Cancer Hospital of Chinese Academy of Medical Sciences from January 2013 to December 2021. Propensity score matching (PSM) was used to minimize the selection bias. Overall survival (OS) and disease-free survival (DFS) were compared between patients receiving BCS and mastectomy.ResultsA total of 994 patients were enrolled, including 285 patients treated with BCS and 709 patients treated with mastectomy. Following PSM, patients were assigned to the BCS (n = 258) and mastectomy (n = 258) groups; these two groups were well balanced regarding clinical and pathological characteristics. The 5-year OS rate (90.5% vs. 95.8%, P = 0.535) and DFS rate (86.3% vs. 86.9%, P = 0.648) of the mastectomy group were identical to those of the BCS group in the matched cohort. Stratified analysis revealed that mastectomy was an independent adverse prognostic factor for OS (hazard ratio [HR]: 2.158, 95% CI: 1.254–4.954, P = 0.034) and DFS (HR: 2.914, 95% CI: 1.713–5.422, P = 0.010) in patients with positive lymph nodes. Additionally, age-based stratification showed that mastectomy was an independent prognostic factor for DFS in BC patients aged > 40 years (HR: 2.471, 95% CI: 1.082–5.643, P = 0.022).ConclusionBCS does not affect OS and DFS in BC patients treated with NAT. However, it should be noted that BCS provides a substantial survival benefit as compared to mastectomy in patients with clinically positive lymph nodes and those aged > 40 years.